Physiological Responses and Adaptations to Lower Load Resistance Training: Implications for Health and Performance - Jonathon Weakley; Brad J. Schoenfeld; Johanna Ljungberg; Shona L. Halson; Stuart M. Phillips (SpringerOpen, 2023)
Abstract Resistance training is a method of enhancing strength, gait speed, mobility, and health. However, the external load required to induce these benefits is a contentious issue. A growing body of evidence suggests that when lower load resistance training [i.e., loads < 50% of one-repetition maximum (1RM)] is completed within close proximity to concentric failure, it can serve as an effective alternative to traditional higher load (i.e., loads > 70% of 1RM) training and in many cases can promote similar or even superior physiological adaptations. Such findings are important given that confidence with external loads and access to training facilities and equipment are commonly cited barriers to regular resistance training. Here, we review some of the mechanisms and physiological changes in response to lower load resistance training. We also consider the evidence for applying lower loads for those at risk of cardiovascular and metabolic diseases and those with reduced mobility. Finally, we provide practical recommendations, specifically that to maximize the benefits of lower load resistance training, high levels of effort and training in close proximity to concentric failure are required. Additionally, using lower loads 2-3 times per week with 3-4 sets per exercise, and loads no lower than 30% of 1RM can enhance muscle hypertrophy and strength adaptations. Consequently, implementing lower load resistance training can be a beneficial and viable resistance training method for a wide range of fitness- and health-related goals.